Fluorine-containing ether compound, lubricant for magnetic recording medium, and magnetic recording medium
By using new hydroxide as lubricant components in magnetic recording media, the problem of decreasing adhesion after thinning of the lubricating layer in the prior art is solved, and high chemical and wear resistance are achieved, which is suitable for further reducing the flight altitude of magnetic recording equipment.
Patent Information
- Application Number
- JP2021567337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-12-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-16
AI Technical Summary
After the lubricating layer of the existing magnetic recording medium is thinned, the adhesion force decreases, resulting in insufficient chemical resistance and wear resistance, making it difficult to meet the further reduction requirements of the magnetic recording and replication equipment for flight altitude.
A novel hydroxide obtained by reacting a phenypropyl or alkylated peroxy compound with sodium hydroxide is used as a lubricant component, which has high adhesion and good chemical and wear resistance.
The new lubricant can maintain high adhesion in the case of thin layers, significantly improve the chemical resistance and wear resistance of magnetic recording media, and extend the service life of the equipment.
Smart Images

Figure 0007647578000035 
Figure 0007647578000001 
Figure 0007647578000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluorine-containing ether compound, a lubricant for a magnetic recording medium, and a magnetic recording medium. This application claims priority based on Japanese Patent Application No. 2019-232037, filed on December 23, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] In order to improve the recording density of magnetic recording and reproducing devices, development of magnetic recording media suitable for high recording density is underway. Conventionally, magnetic recording media include those in which a recording layer is formed on a substrate and a protective layer such as carbon is formed on the recording layer. The protective layer protects the information recorded on the recording layer and also improves the sliding properties of the magnetic head. However, the durability of the magnetic recording medium cannot be sufficiently obtained by simply providing a protective layer on the recording layer. For this reason, a lubricant is generally applied to the surface of the protective layer to form a lubricating layer.
[0003] As lubricants for use in forming a lubricating layer on a magnetic recording medium, for example, those containing a compound having a polar group such as a hydroxyl group or an amino group at the end of a fluorine-based polymer having a repeating structure containing CF2 have been proposed. For example, Patent Documents 1 and 2 disclose compounds in which perfluoropolyethers are bonded to both sides of an aliphatic hydrocarbon chain having a hydroxyl group in the center of the molecule. Patent Document 3 discloses a fluorine-containing ether compound in which divalent linking groups having polar groups are linked to both ends of a perfluoropolyether chain, and at least one of the chains is linked to an end group which is an organic group having 1 to 8 carbon atoms and in which at least one hydrogen atom of the organic group has been substituted with a cyano group. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] U.S. Patent No. 9,805,755 [Patent Document 2] International Publication No. 2016 / 084781 [Patent Document 3] International Publication No. 2019 / 039200 Summary of the Invention [Problem to be solved by the invention]
[0005] In magnetic recording and reproducing devices, there is a demand for an even smaller flying height of the magnetic head, which in turn requires a thinner lubricating layer in the magnetic recording medium. However, generally, when the thickness of the lubricating layer is reduced, the adhesion of the lubricating layer decreases, and the chemical resistance and abrasion resistance of the magnetic recording medium tend to decrease.
[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a fluorine-containing ether compound which can form a lubricating layer that has excellent adhesion even when thin and has good chemical resistance and abrasion resistance, and which can be suitably used as a material for a lubricant for a magnetic recording medium. Another object of the present invention is to provide a lubricant for magnetic recording media which contains the fluorinated ether compound of the present invention and is capable of forming a lubricating layer having excellent adhesion, resistance to chemicals, and abrasion resistance. Another object of the present invention is to provide a magnetic recording medium having excellent reliability and durability, which is provided with a lubricating layer containing the fluorinated ether compound of the present invention. [Means for solving the problem]
[0007] The present invention includes the following first aspect. [1] A fluorinated ether compound represented by the following formula (1): R 1 -R 2 -CH2-R 3 -CH2-OCH2CH(OH)CH2O-CH2-R 3 -CH2-R 4 -R5 (1) (In formula (1), R 3 is a perfluoropolyether chain; R 2 and R 4 are divalent linking groups having a polar group, which may be the same or different; R 1 and R 5 is R 2 or R 4 are terminal groups bonded to oxygen atoms of R 1 and R 5 At least one of the above is an organic group having 1 to 8 carbon atoms, and at least one of the hydrogen atoms of the organic group is substituted with a cyano group.
[0008] The compound according to the first aspect of the present invention preferably includes the features described in the following items [2] to
[13] . It is also preferable to combine two or more of these features. [2] The fluorine-containing ether compound according to [1], wherein the organic group is a phenyl group or an alkyl group having 1 to 5 carbon atoms. [3] The fluorine-containing ether compound according to [1] or [2], wherein the polar group is a hydroxyl group. [4] R in the above formula (1) 2 The hydroxyl group contained in R 4 The fluorine-containing ether compound according to [3], wherein the total number of hydroxyl groups contained in
[0009] [5] R in the above formula (1) 2 and R 4 The fluorine-containing ether compound according to any one of [1] to [4], which contains 1 to 3 linking groups represented by the following formula (2): -CH2CH(OH)CH2- (2) [6] R in the above formula (1) 2 and R 4 is a linking group represented by the following formula (2-1): -OX-(Y 1 X) a -Y 2 - (2-1) (In formula (2-1), a represents an integer of 0 to 2; X represents formula (2); Y 1 represents any one selected from -O-, -CH2-, -CH2O-, and -OCH2-; Y 2 represents -O- or -CH2O-.) [7] Y in the above formula (2-1) 1 and Y 2 The fluorine-containing ether compound according to [6], wherein
[0010] [8] R in the above formula (1) 3 is any one selected from perfluoropolyether chains represented by the following formulas (3) to (5): -CF2-(OCF2CF2) b -(OCF2) c -OCF2- (3) (In formula (3), b and c represent the average degree of polymerization, b represents 1 to 20, and c represents 0 to 20.) -CF2CF2-(OCF2CF2CF2) d -OCF2CF2- (4) (In formula (4), d represents the average degree of polymerization and represents 1 to 20.) -CF2CF2CF2-(OCF2CF2CF2CF2) e -OCF2CF2CF2- (5) (In formula (5), e represents the average degree of polymerization and represents 1 to 10.)
[0011] [9] R in the above formula (1) 1 and R 5 is a phenyl group or an alkyl group having 1 to 5 carbon atoms substituted with at least one cyano group.
[10] In the formula (1), R 3 The two perfluoropolyether chains represented by R 2 and R 4 is the same, and R 1 and R 5 The fluorine-containing ether compound according to any one of [1] to [9], wherein
[11] R in the above formula (1) 1 and R 5 the fluorine-containing ether compound according to any one of [1] to [8], wherein one of the above is a phenyl group or an alkyl group having 1 to 5 carbon atoms substituted with at least one cyano group, and the other is an organic group having at least one group containing an aromatic hydrocarbon, a group containing an aromatic heterocycle, an alkenyl group or an alkynyl group.
[0012]
[12] The fluorine-containing ether compound according to [1], which is any of the compounds represented by the following formulas (A) to (P):
[0013] [ka] (In formula (A), ma1, ma2, na1, and na2 represent average degrees of polymerization, ma1 and ma2 represent 1 to 20, and na1 and na2 represent 0 to 20.) (In formula (B), mb1, mb2, nb1, and nb2 represent average degrees of polymerization, mb1 and mb2 represent 1 to 20, and nb1 and nb2 represent 0 to 20.) (In formula (C), mc1, mc2, nc1, and nc2 represent average degrees of polymerization, mc1 and mc2 represent 1 to 20, and nc1 and nc2 represent 0 to 20.) (In formula (D), md1, md2, nd1, and nd2 represent average degrees of polymerization, md1 and md2 represent 1 to 20, and nd1 and nd2 represent 0 to 20.)
[0014] [ka] (In formula (E), me1, me2, ne1, and ne2 represent average degrees of polymerization, me1 and me2 represent 1 to 20, and ne1 and ne2 represent 0 to 20.) (In formula (F), mf1, mf2, nf1, and nf2 represent average degrees of polymerization, mf1 and mf2 represent 1 to 20, and nf1 and nf2 represent 0 to 20.) (In formula (G), mg1, mg2, ng1, and ng2 represent average degrees of polymerization, mg1 and mg2 represent 1 to 20, and ng1 and ng2 represent 0 to 20.) (In formula (H), mh1, mh2, nh1, and nh2 represent average degrees of polymerization, mh1 and mh2 represent 1 to 20, and nh1 and nh2 represent 0 to 20.)
[0015] [ka] (In formula (I), mi1, mi2, ni1, and ni2 represent average degrees of polymerization, mi1 and mi2 represent 1 to 20, and ni1 and ni2 represent 0 to 20.) (In formula (J), mj1, mj2, nj1, and nj2 represent average degrees of polymerization, mj1 and mj2 represent 1 to 20, and nj1 and nj2 represent 0 to 20.) (In formula (K), mk1, mk2, nk1, and nk2 represent average degrees of polymerization, mk1 and mk2 represent 1 to 20, and nk1 and nk2 represent 0 to 20.) (In formula (L), ml1, ml2, nl1, and nl2 represent average degrees of polymerization, ml1 and ml2 represent 1 to 20, and nl1 and nl2 represent 0 to 20.)
[0016] [ka] (In formula (M), mm1, mm2, nm1, and nm2 represent average degrees of polymerization, mm1 and mm2 represent 1 to 20, and nm1 and nm2 represent 0 to 20.) (In formula (N), mn1, mn2, nn1, and nn2 represent average degrees of polymerization, mn1 and mn2 represent 1 to 20, and nn1 and nn2 represent 0 to 20.) (In formula (O), po1 and po2 each represent an average degree of polymerization, and each represents 1 to 20.) (In formula (P), qp1 and qp2 each represent an average degree of polymerization and are 1 to 10.)
[0017]
[13] The fluorinated ether compound according to any one of [1] to
[12] , having a number average molecular weight in the range of 500 to 10,000.
[0018] A second aspect of the present invention is the following lubricant.
[14] A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of [1] to
[13] . A third aspect of the present invention is a magnetic recording medium as follows.
[15] A magnetic recording medium having at least a magnetic layer, a protective layer, and a lubricating layer provided in that order on a substrate, 2. A magnetic recording medium, wherein the lubricating layer contains the fluorine-containing ether compound according to any one of [1] to
[13] . The above magnetic recording medium preferably includes the following features.
[16] The magnetic recording medium according to
[15] , wherein the average thickness of the lubricating layer is 0.5 nm to 2.0 nm. Effect of the Invention
[0019] The fluorine-containing ether compound of the present invention is a compound represented by the above formula (1), and is suitable as a material for a lubricant for a magnetic recording medium. The lubricant for magnetic recording media of the present invention contains the fluorine-containing ether compound of the present invention, and therefore can form a lubricating layer that has excellent adhesion even when thin, and has good resistance to chemicals and abrasion resistance. The magnetic recording medium of the present invention has excellent adhesion due to the inclusion of the fluorine-containing ether compound of the present invention, and is provided with a lubricating layer having good chemical resistance and abrasion resistance, and therefore has excellent reliability and durability. [Brief description of the drawings]
[0020] [Figure 1] 1 is a schematic cross-sectional view showing a preferred embodiment of a magnetic recording medium of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Preferred examples of the fluorine-containing ether compound, lubricant and magnetic recording medium of the present invention will now be described in detail. The present invention is not limited to the following embodiments. For example, the number, type, composition, position, amount, ratio, material, configuration, and the like can be added, omitted, substituted, or changed without departing from the spirit of the present invention. Conventionally, as a material for a lubricant for magnetic recording media (hereinafter sometimes abbreviated as "lubricant") to be applied to the surface of a protective layer, a fluorine-containing ether compound having a polar group such as a hydroxyl group at the end of a chain structure is preferably used. The polar group in the fluorine-containing ether compound bonds with an active site on the protective layer to improve the adhesion (adhesion) of the lubricant layer to the protective layer. For this reason, as a material for a lubricant, a fluorine-containing ether compound having a polar group not only at the end of the chain structure but also in the chain structure is particularly preferably used.
[0022] However, when a thin lubricating layer is formed on a protective layer using a conventional lubricant, it is difficult to realize a lubricating layer that has excellent adhesion and good chemical resistance and wear resistance, as will be described below. That is, if the adhesion of the lubricant to the protective layer (the adhesion of the lubricant layer) is insufficient, the lubricant applied on the protective layer will be bulky. Therefore, the lubricant layer is likely to be unevenly coated on the protective layer. If the lubricant layer is unevenly coated, the chemical resistance and wear resistance of the lubricant layer will be insufficient. Therefore, if the adhesion of the lubricant layer is insufficient, the film thickness must be increased to make the lubricant layer evenly coated on the protective layer, otherwise sufficient chemical resistance and wear resistance cannot be obtained.
[0023] One possible method for improving the adhesion of a lubricant to a protective layer (the adhesion of the lubricant layer) is to use, as a lubricant material, a fluorine-containing ether compound in which polar groups are bonded to the most terminal carbon atom of a chain structure, the carbon atom bonded to the most terminal carbon atom, and other carbon atoms in the chain structure. However, in the case of a lubricating layer formed using such a fluorine-containing ether compound, the adhesion to the protective layer is too strong, which may impair the lubricating properties and result in insufficient abrasion resistance.
[0024] The adhesion of the lubricant to the protective layer can be adjusted, for example, by changing the heat treatment temperature in the heat treatment that is carried out as necessary after the lubricant containing the fluorine-containing ether compound is applied onto the protective layer. Specifically, the adhesion of the lubricant to the protective layer is strengthened by increasing the heat treatment temperature, and is weakened by decreasing the heat treatment temperature. Therefore, if the adhesion of the lubricant to the protective layer is too strong, the adhesion between the lubricating layer and the protective layer can be weakened by, for example, lowering the heat treatment temperature, and the adhesion between the lubricating layer and the protective layer can be adjusted to an appropriate strength, thereby improving the wear resistance of the lubricating layer.
[0025] However, in the lubricating layer formed by using the fluorine-containing ether compound, the carbon atom at the most terminal of the chain structure, the carbon atom bonded to the carbon atom at the most terminal, and the carbon atom in the other chain structure are bonded with polar groups, if the adhesion with the protective layer is weakened by using the above-mentioned method, the chemical resistance of the lubricating layer is deteriorated.This is presumed to be because the proportion of the polar groups in the fluorine-containing ether compound that are not involved in the bond with the active site on the protective layer increases.In other words, it is presumed that the polar groups in the fluorine-containing ether compound that are not involved in the bond with the active site on the protective layer attract environmental substances that generate pollutants to the lubricating layer, and deteriorate the chemical resistance of the lubricating layer.
[0026] Therefore, the present inventors focused on the bond between the polar group contained in the fluorine-containing ether compound and the active site on the protective layer, and conducted extensive research to realize a fluorine-containing ether compound that is less likely to produce polar groups that are not involved in the bond with the active site on the protective layer, has a uniform coating state with good adhesion to the protective layer, and can form a lubricating layer with good chemical resistance and wear resistance. As a result, it was found that a fluorine-containing ether compound may be obtained in which a glycerin structure is located at the center of a chain structure, and on both sides of the chain structure, a perfluoropolyether chain, a methylene group, a divalent linking group having a polar group, and an end group are bonded in this order via a methylene group (-CH2-), and at least one of the end groups is an organic group having 1 to 8 carbon atoms, and at least one hydrogen of the organic group is substituted with a cyano group.
[0027] In such a fluorine-containing ether compound, the carbon of the cyano group (-CN) contained in at least one of the terminal groups is an SP hybrid orbital, and therefore has difficulty in free rotation. Therefore, the interaction (affinity) of the cyano group contained in at least one of the terminal groups with the protective layer is weaker than that of the hydroxyl group of the glycerin structure and the polar group of the divalent linking group. Therefore, in the above-mentioned fluorine-containing ether compound, the cyano group contained in at least one end group, the hydroxyl group of glycerin structure, and the polar group of divalent linking group each independently show good interaction with protective layer, and each independently can bond with the functional group (active point) that exists in large number on protective layer.From these points, it is estimated that the above-mentioned fluorine-containing ether compound can form a lubricating layer that has good adhesion to protective layer.
[0028] In addition, in the above-mentioned fluorine-containing ether compound, a perfluoropolyether chain is arranged between the glycerin structure arranged in the center of the chain structure and the two divalent linking groups. Therefore, the distance between the hydroxyl group (-OH) of the glycerin structure and the polar group of the divalent linking group is appropriate. Moreover, at least one of the terminal groups is an organic group having one or more cyano groups that are difficult to rotate freely. For these reasons, the hydroxyl group of the glycerin structure and the polar group of the divalent linking group are unlikely to be inhibited by adjacent polar groups from binding to active points on the protective layer. Therefore, the hydroxyl group of the glycerin structure and the polar group of the divalent linking group are both likely to be involved in binding to active points on the protective layer, and are unlikely to become polar groups that are not involved in binding to active points on the protective layer. Therefore, in the above-mentioned fluorine-containing ether compound, the number of polar groups that are not involved in binding to active points on the protective layer can be suppressed, and the deterioration of chemical resistance and the occurrence of pick-up can be suppressed.
[0029] In addition, in the above-mentioned fluorine-containing ether compound, the distance between the hydroxyl group of the glycerin structure and the polar group of the divalent linking group is appropriate, so that the hydroxyl group of the glycerin structure is not easily aggregated with the polar group of the divalent linking group. Moreover, both ends of each perfluoropolyether chain are adhered to the protective layer by the hydroxyl group of the glycerin structure and the polar group of the divalent linking group. Therefore, the state of the fluorine-containing ether compound applied on the protective layer is not easily bulky, and the fluorine-containing ether compound is easily wetted and spread on the protective layer, and a lubricating layer having a uniform coating state is easily obtained. Therefore, the above-mentioned fluorine-containing ether compound can form a lubricating layer with good chemical resistance and wear resistance.
[0030] Furthermore, the present inventors have confirmed that by using a lubricant containing the above-mentioned fluorine-containing ether compound, a lubricating layer that has excellent adhesion even when thin and has good chemical resistance and wear resistance can be formed, and have arrived at the present invention.
[0031] Preferred examples of the fluorine-containing ether compound, the lubricant for a magnetic recording medium, and the magnetic recording medium of the present invention will be described in detail below. Note that the present invention is not limited to only the embodiments shown below.
[0032] [Fluorine-containing ether compounds] The fluorine-containing ether compound of the present embodiment is represented by the following formula (1). R 1 -R 2 -CH2-R 3 -CH2-OCH2CH(OH)CH2O-CH2-R 3 -CH2-R 4 -R 5 (1) (In formula (1), R 3 is a perfluoropolyether chain; R 2 and R 4 are divalent linking groups having a polar group, which may be the same or different; R 1 and R 5 is R 2 or R 4 are terminal groups bonded to oxygen atoms of R 1 and R 5 At least one of the above is an organic group having 1 to 8 carbon atoms, and at least one of the hydrogen atoms of the organic group is substituted with a cyano group.
[0033] As shown in formula (1), the fluorinated ether compound of the present embodiment has a glycerin structure at the center of a chain structure, and on both sides of the chain structure, R 3 A perfluoropolyether chain (hereinafter sometimes abbreviated as "PFPE chain") represented by the formula: 2 and R 4 and a divalent linking group having a polar group represented by R 1 and R 5 In formula (1), R 1 and R 5At least one of the terminal groups is an organic group having 1 to 8 carbon atoms, and at least one of the hydrogen atoms of the organic group is substituted with a cyano group (hereinafter, sometimes referred to as an "organic group substituted with a cyano group").
[0034] (Glycerin structure) In the fluorinated ether compound represented by formula (1), the hydroxyl group (-OH) of the glycerin structure (-OCH2CH(OH)CHO-) located in the center of the chain structure bonds the fluorinated ether compound to the protective layer, forming a thin lubricating layer with sufficient coverage. In addition, the oxygen atoms at both ends of the glycerin structure form ether bonds (-O-) with the methylene groups (-CH2-) on both sides of the oxygen atoms. These two ether bonds impart appropriate flexibility to the fluorine-containing ether compound represented by formula (1) and increase the affinity between the hydroxyl groups of the glycerin structure and the protective layer.
[0035] (R 3 (PFPE chain represented by In the fluorine-containing ether compound represented by formula (1), R 3 When the lubricant containing the fluorine-containing ether compound of this embodiment is applied onto a protective layer to form a lubricating layer, the PFPE chain shown in (a) coats the surface of the protective layer and imparts lubricity to the lubricating layer to reduce the friction between the magnetic head and the protective layer. The PFPE chain is appropriately selected according to the performance required for the lubricant containing the fluorine-containing ether compound. The PFPE chain may be a polymer or copolymer of perfluoroalkylene oxide, such as perfluoromethylene oxide, perfluoroethylene oxide, perfluoro-n-propylene oxide, or perfluorobutylene oxide.
[0036] Specifically, R in formula (1) 3 R is preferably any one selected from the PFPE chains represented by the following formulas (3) to (5). 3When R is any one selected from the PFPE chains represented by formulas (3) to (5), the resulting fluorine-containing ether compound provides a lubricating layer having good lubricity. 3 When R is any one of the PFPE chains represented by formulas (3) to (5), the ratio of the number of oxygen atoms (the number of ether bonds (-O-)) to the number of carbon atoms in the PFPE chain is appropriate. This results in a fluorine-containing ether compound with appropriate hardness. Therefore, the fluorine-containing ether compound applied onto the protective layer is less likely to aggregate on the protective layer, and a thinner lubricating layer can be formed with a sufficient coverage. 3 is particularly preferably a PFPE chain represented by formula (3), since this is a fluorine-containing ether compound that has appropriate flexibility and can form a lubricating layer with better chemical resistance and wear resistance.
[0037] -CF2-(OCF2CF2) b -(OCF2) c -OCF2- (3) (In formula (3), b and c represent the average degree of polymerization, b represents 1 to 20, and c represents 0 to 20.) -CF2CF2-(OCF2CF2CF2) d -OCF2CF2- (4) (In formula (4), d represents the average degree of polymerization and represents 1 to 20.) -CF2CF2CF2-(OCF2CF2CF2CF2) e -OCF2CF2CF2- (5) (In formula (5), e represents the average degree of polymerization and represents 1 to 10.)
[0038] In formula (3), the arrangement order of the repeating units (OCF2CF2) and (OCF2) is not particularly limited. In formula (3), the number b of (OCF2CF2) and the number c of (OCF2) may be the same or different. The PFPE chain represented by formula (3) may be a polymer of (OCF2CF2). In addition, the PFPE chain represented by formula (3) may be any of a random copolymer, a block copolymer, and an alternating copolymer composed of (OCF2CF2) and (OCF2).
[0039] In formulas (4) to (5), d, which indicates the average degree of polymerization, is 1 to 20, and e is 1 to 10 (or in formula (3), b is 1 to 20, and c is 0 to 20), so that the fluorine-containing ether compound can provide a lubricating layer having good lubricity. In formulas (3) to (5), b, c, and d, which indicate the average degree of polymerization, are 20 or less, and e is 10 or less, so that the viscosity of the fluorine-containing ether compound is not too high, and the lubricant containing the fluorine-containing ether compound is easy to apply, which is preferable. b, c, d, and e, which indicate the average degree of polymerization, are preferably 2 to 10, and more preferably 3 to 7, so that the fluorine-containing ether compound can easily wet and spread on the protective layer and can easily provide a lubricating layer having a uniform thickness.
[0040] In the fluorine-containing ether compound represented by formula (1), R 3 The two PFPE chains represented by may be the same or different.
[0041] (R 2 and R 4 (a divalent linking group having a polar group represented by the formula: In the fluorine-containing ether compound represented by formula (1), R 2 and R 4 is a divalent linking group having a polar group. In the fluorine-containing ether compound represented by formula (1), R 2 and R 4 Since R has a polar group, when a lubricating layer is formed on a protective layer using a lubricant containing this, a favorable interaction occurs between the lubricating layer and the protective layer. 2 and R 4 The divalent linking group having a polar group constituting the formula (I) can be appropriately selected depending on the performance required of the lubricant containing the fluorine-containing ether compound.
[0042] R 2 and R 4Examples of the polar group of the divalent linking group having a polar group represented by the formula include a hydroxyl group (-OH), an amino group (-NH2), a carboxyl group (-COOH), an aldehyde group (-COH), a carbonyl group (-CO-), and a sulfonic acid group (-SO3H). Among these, it is particularly preferable that the polar group is a hydroxyl group. The hydroxyl group has a strong interaction with a protective layer, particularly a protective layer formed of a carbon-based material. Therefore, R 2 and / or R 4 When the polar group is a hydroxyl group, the lubricating layer containing a fluorine-containing ether compound has high adhesion (tight adhesion) to the protective layer.
[0043] R 2 and / or R 4 When the polar group of contains a hydroxyl group, R 2 The hydroxyl group and R 4 The total number of hydroxyl groups contained in R is preferably 2 to 6, more preferably 2 to 5, and even more preferably 3 to 4. When the total number of hydroxyl groups contained in R is 2 or more, 2 and R 4 The interaction between the hydroxyl groups and the protective layer is more effectively obtained. As a result, the fluorine-containing ether compound can form a lubricating layer with higher adhesion (tightness) to the protective layer. In addition, when the total number of the hydroxyl groups is 6 or less, the polar groups that are not involved in the bond between the lubricating layer and the active sites on the protective layer can be prevented from attracting environmental substances that generate pollutants to the lubricating layer, thereby suppressing pick-up.
[0044] R 2 and / or R 4 preferably contains 1 to 3 linking groups represented by the following formula (2), R 2 and R 4 More preferably, contains 1 to 3 linking groups represented by the following formula (2). -CH2CH(OH)CH2- (2)
[0045] The linking group represented by formula (2) is a linking group having a hydroxyl group, which is a polar group that has a particularly large interaction with the protective layer. In addition, in the linking group represented by formula (2), methylene groups (-CH2-) are arranged on both sides of the carbon atom to which the hydroxyl group is bonded. For this reason, R 2 and / or R 4 When contains 1 to 3 linking groups represented by formula (2), the resulting fluorine-containing ether compound provides a lubricating layer with even higher adhesion (tightness) to the protective layer for the reasons described below.
[0046] That is, the carbon atom to which the hydroxyl group of the linking group represented by formula (2) is bonded and R 1 or R 5 Between the methylene group and R 2 or R 4 Therefore, at least an oxygen atom (-O-) contained in the linking group represented by formula (2) and an oxygen atom (-O-) contained in R 1 and / or R 5 Therefore, the distance between the hydroxyl group of the linking group represented by formula (2) and the cyano group of R 1 and / or R 5 and the terminal groups represented by the formula (1) each independently exhibit good interaction with the protective layer, and each independently easily bonds with a large number of functional groups (active sites) present on the protective layer.
[0047] In addition, in the linking group represented by formula (2), methylene groups are arranged on both sides of the carbon atom to which the hydroxyl group is bonded, so that R 2 and / or R 4 When the linking group represented by formula (2) is comprised of 2 to 3, the distance between the hydroxyl groups contained in the linking group represented by formula (2) becomes appropriate. As a result, even if the linking group represented by formula (2) contains a plurality of hydroxyl groups, each of the hydroxyl groups contained in the linking group represented by formula (2) is likely to participate in bonding with the active site on the protective layer.
[0048] Also, R 2 and / or R 4 When R contains 1 to 3 linking groups represented by formula (2), 2and / or R 4 contains 1 to 3 hydroxyl groups. 2 and / or R 4 This tends to make the number of hydroxyl groups contained in the fluorine-containing ether compound appropriate, and prevents the polarity of the fluorine-containing ether compound from becoming too high, thereby preventing the occurrence of pick-up.
[0049] The number of linking groups represented by formula (2) is set to be 1 or less, so that a fluorine-containing ether compound can be obtained that provides a lubricating layer having even better adhesion to a protective layer. 2 The hydroxyl group and R 4 The total number of hydroxyl groups contained in is preferably adjusted to 2 to 5, and more preferably 3 to 4.
[0050] R 2 and / or R 4 is preferably a linking group represented by the following formula (2-1), and R 2 and R 4 is more preferably a linking group represented by the following formula (2-1): 1 or R 5 is an oxygen atom bonded to -OX-(Y 1 X) a -Y 2 - (2-1) (In formula (2-1), a represents an integer of 0 to 2; X represents formula (2); Y 1 represents any one selected from -O-, -CH2-, -CH2O-, and -OCH2-; Y 2 represents -O- or -CH2O-.)
[0051] R 2 and / or R 4 is a linking group represented by formula (2-1), it is preferable because it results in a fluorine-containing ether compound that is easy to synthesize.
[0052] In the linking group represented by formula (2-1), a in formula (2-1) is an integer of 0 to 2. Since a in the linking group represented by formula (2-1) is 0 or more, R2 and / or R 4 When the linking group is represented by formula (2-1), it contains one or more hydroxyl groups as polar groups, which have a particularly strong interaction with the protective layer. As a result, the fluorine-containing ether compound can provide a lubricating layer with better adhesion to the protective layer. In addition, since the linking group represented by formula (2-1) has a value of a of 2 or less, the polarity of the fluorine-containing ether compound becomes too high due to the large number of hydroxyl groups in the linking group represented by formula (2-1), and the lubricant containing the fluorine-containing ether compound can be prevented from picking up as a foreign matter (smear).
[0053] In addition, in the case of the linking group represented by formula (2-1), when a in formula (2-1) is 1 or 2, the distance between the hydroxyl groups contained in the linking group represented by formula (2-1) becomes appropriate. 2 and / or R 4 Even if there are multiple hydroxyl groups in R 2 and / or R 4 The hydroxyl groups contained in each of the above are easily involved in bonding with the active sites on the protective layer.
[0054] In the linking group represented by formula (2-1), X in formula (2-1) is formula (2), and Y 1 represents any one selected from -O-, -CH2-, -CH2O-, and -OCH2-; Y 2 represents -O- or -CH2O-. Y 1 and Y 2 may be the same or different from each other. R 2 and / or R 4 is a linking group represented by formula (2-1), R 2 and R 1 , and / or R 4 and R 5 and are bonded by ether bonds, and R 2 and R 3 Between and / or R 4 and R 3As a result, a fluorine-containing ether compound having appropriate flexibility is obtained, and a lubricating layer having better chemical resistance and wear resistance can be formed.
[0055] In the linking group represented by formula (2-1), Y 1 is preferably an ether bond (—O—) or a group containing an ether bond, and Y 1 and Y 2 It is more preferable that Y is -O-. 1 is CH2, the resulting fluorine-containing ether compound has appropriate flexibility. Therefore, the interaction between the hydroxyl group contained in the linking group represented by formula (2-1) and the protective layer becomes stronger.
[0056] In the fluorine-containing ether compound represented by formula (1), R 2 and R 4 may be the same or different.
[0057] (R 1 and R 5 (end group represented by In the fluorine-containing ether compound represented by formula (1), R 1 and R 5 At least one of the terminal groups represented by the formula (I) is an organic group having 1 to 8 carbon atoms, and at least one hydrogen atom of the organic group is substituted with a cyano group (-CN) (an organic group substituted with a cyano group). In the fluorine-containing ether compound represented by formula (1), the cyano group contained in the organic group substituted with a cyano group exhibits a moderate interaction with the protective layer. Therefore, the organic group substituted with a cyano group has the function of improving the adhesion between the lubricating layer and the protective layer, and forming a lubricating layer with good chemical resistance and wear resistance.
[0058] In the fluorine-containing ether compound represented by formula (1), the type of organic group substituted with a cyano group can be appropriately selected depending on the performance required of a lubricant containing the fluorine-containing ether compound. The number of cyano groups in the organic group substituted with a cyano group is not particularly limited and may be 1 or 2 or more. The number of cyano groups in the organic group substituted with a cyano group is preferably 1, since this results in a fluorine-containing ether compound that is relatively easy to produce.
[0059] The organic group in the organic group substituted with a cyano group has a carbon atom number of 1 to 8. In the fluorine-containing ether compound represented by formula (1), since the carbon atom number is 1 to 8, the organic group substituted with a cyano group does not become a steric hindrance, and the fluorine-containing ether compound has good affinity between the cyano group and the protective layer. The organic group in the organic group substituted with a cyano group is preferably a phenyl group or an alkyl group having 1 to 8 carbon atoms, and more preferably a phenyl group or an alkyl group having 1 to 5 carbon atoms. When the organic group in the organic group substituted with a cyano group is a phenyl group or an alkyl group having 1 to 5 carbon atoms, the steric hindrance of the organic group in the organic group substituted with a cyano group is more effectively suppressed, resulting in a fluorine-containing ether compound with high affinity between the cyano group and the protective layer.
[0060] Specifically, examples of the organic group substituted with a cyano group include any of the organic groups represented by the following formulae (6-1) to (6-4) and (7) to (11). The dotted lines in formulas (6-1) to (6-4) and formulas (7) to (11) represent R 2 or R 4 is a bond bonded to
[0061] [ka]
[0062] Among the organic groups substituted with a cyano group represented by formulas (6-1) to (6-4) and formulas (7) to (11), it is preferable to use any of the organic groups selected from the organic groups represented by formulas (6-1) and (7) to (10) in order to obtain a fluorine-containing ether compound that exhibits good affinity with the protective layer of a magnetic recording medium, it is more preferable to use the organic group represented by formula (6-1) or the organic group represented by formula (10) in order to obtain a fluorine-containing ether compound that is relatively easy to produce, and the organic group represented by formula (6-1) is most preferable.
[0063] In the fluorine-containing ether compound represented by formula (1), R 1 and R 5 When both of the terminal groups represented by R 1 and R 5 may be the same or different.
[0064] In the fluorine-containing ether compound represented by formula (1), R 1 and R 5 One of the terminal groups represented by (e.g., R 5 When only one end group is an organic group substituted with a cyano group, the other end group (e.g., R 1 ) may be any group, and is not particularly limited. 1 and R 5 When only one of the terminal groups represented by is an organic group substituted with a cyano group, the other terminal group is preferably an organic group having at least one double bond or triple bond, such as a group containing an aromatic hydrocarbon, a group containing an aromatic heterocycle, a group containing an alkenyl group, a group containing an alkynyl group, etc. The other terminal group may contain a hydroxyl group, but it is preferable that it does not contain a hydroxyl group in order to prevent the wear resistance of the lubricating layer from being impaired due to the number of hydroxyl groups being too large.
[0065] Specifically, the other terminal group may be a phenyl group, a methoxyphenyl group, a fluorinated phenyl group, a naphthyl group, a phenethyl group, a methoxyphenethyl group, a fluorinated phenethyl group, a benzyl group, a methoxybenzyl group, a naphthylmethyl group, a methoxynaphthyl group, a pyrrolyl group, a pyrazolyl group, a methylpyrazolylmethyl group, an imidazolyl group, a furyl group, a furfuryl group, an oxazolyl group, an isoxazolyl group, a thienyl group, a thienylethyl group, a thiazolyl group, a methylthiazolylethyl group, an isothiazolyl group, a pyridyl group, a pyrimidinyl group, or a pyridazinyl group. The alkyl group may be a group selected from the group consisting of aryl, pyrazinyl, indolinyl, benzofuranyl, benzothienyl, benzimidazolyl, benzoxazolyl, benzothiazolyl, benzopyrazolyl, benzoisoxazolyl, benzoisothiazolyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, cinnolinyl, vinyl, allyl, butenyl, propynyl, propargyl, butynyl, methylbutynyl, pentynyl, methylpentynyl, and hexynyl.
[0066] The other end group is preferably any one of the above-mentioned groups, particularly a phenyl group, a methoxyphenyl group, a thienylethyl group, a butenyl group, an allyl group, a propargyl group, a phenethyl group, a methoxyphenethyl group, and a fluorinated phenethyl group. In this case, the fluorine-containing ether compound can form a lubricating layer having superior chemical resistance and wear resistance. The other end group may have a substituent such as an alkyl group, an alkoxy group, a hydroxyl group, a thiol group, a carboxyl group, a carbonyl group or an amino group.
[0067] In the fluorine-containing ether compound represented by formula (1), R 1 and R 5 When only one of the terminal groups represented by R 1 and R 5It is preferable that one of the above is a phenyl group or an alkyl group having 1 to 5 carbon atoms substituted with at least one cyano group, and the other is an organic group having at least one group containing an aromatic hydrocarbon, a group containing an aromatic heterocycle, an alkenyl group, or an alkynyl group. Such a fluorine-containing ether compound can form a lubricating layer having good chemical resistance and wear resistance.
[0068] In the fluorine-containing ether compound represented by formula (1), R 3 The two PFPE chains represented by R 2 and R 4 Same for R. 1 and R 5 In addition, since such a fluorine-containing ether compound has a symmetric structure with the glycerin structure at the center, it is easy to wet and spread evenly on the protective layer, and a lubricating layer having a uniform thickness is easily obtained, which is preferable.
[0069] Specifically, the fluorine-containing ether compound represented by formula (1) is preferably any of the compounds represented by the following formulae (A) to (P). Note that ma1 to mn1, ma2 to mn2, na1 to nn1, na2 to nn2, po1, po2, qp1, and qp2 in formulae (A) to (P) are values indicating the average degree of polymerization, and are not necessarily integers. When the compound represented by formula (1) is any of the compounds represented by the above formulas (A) to (P), it is preferable because the raw materials are easily available, and a lubricating layer can be formed that has excellent adhesion even if it is thin, and has even better chemical resistance and wear resistance.
[0070] The compounds represented by the following formulas (A) to (P) are all represented by the formula (1) R 3 The two PFPE chains represented by the following formulas (A) to (P) are all the same. 2 and R 4 is a linking group represented by the above formula (2-1), and Y 2 is -O-. The compounds represented by the following formulas (A) to (E) are all R 1 and R 5 is an organic group represented by the above formula (6-1), and R 2 and R 4 is a linking group represented by the above formula (2-1), and R 3 is expressed by equation (3).
[0071] The compounds represented by formulas (A) to (C) are all R 2 In the above formula (2-1), a is 0. The compound represented by formula (A) is 4 In the above formula (2-1), a is 0, and the compound represented by formula (B) is R 4 In the above formula (2-1), a is 1, Y 1 is -O-, and the compound represented by formula (C) is 4 In the above formula (2-1), a is 2, Y 1 is -O-. The compounds represented by formula (D) and (E) are both R 2 In the above formula (2-1), a is 1, Y 1 is -O-. The compound represented by formula (D) is 4 In the above formula (2-1), a is 1, Y 1 is -O-, and the compound represented by formula (E) is R 4 In the above formula (2-1), a is 2, Y 1 is -O-.
[0072] The compounds represented by the following formulas (F), (G), and (I) are R 2 and R 4 is a linking group represented by the above formula (2-1), in which a in formula (2-1) is 1, Y 1 is -O- and R 3 is expressed by equation (3). The compound represented by formula (F) is R 1 and R 5 is the above formula (8), and the compound represented by formula (G) is R 1 and R 5 is the above formula (9), and the compound represented by formula (I) is R 1 and R 5is the above formula (10).
[0073] The compound represented by the following formula (H) is R 1 and R 5 is the above formula (7), and R 2 and R 4 is a linking group represented by the above formula (2-1), in which a in formula (2-1) is 0, and R 3 is expressed by equation (3).
[0074] The compounds represented by the following formulas (J) to (N) are all R 1 is an organic group represented by the above formula (6-1), and R 2 and R 4 is a linking group represented by the above formula (2-1), and R 3 is expressed by equation (3). The compounds represented by the formulas (J) and (L) to (N) are all R 2 and R 4 In the above formula (2-1), a is 1, Y 1 is -O-. The compound represented by formula (K) is 2 In the above formula (2-1), a is 1, Y 1 is -O- and R 4 In the above formula (2-1), a is 0. The compound represented by formula (J) is R 5 is the above formula (9), and the compound represented by formula (K) is R 5 is the above formula (10), and the compound represented by formula (L) is R 5 is an allyl group, and the compound represented by formula (M) is 5 is a phenyl group, and the compound represented by formula (N) is 5 is a thienylethyl group.
[0075] The compounds represented by the following formulas (O) and (P) are both R 1 and R 5 is an organic group represented by the above formula (6-1), and R 2 and R 4 is a linking group represented by the above formula (2-1), in which a in (2-1) is 1, Y 1is -O-. The compound represented by formula (O) is 3 is represented by formula (4). The compound represented by formula (P) is 3 is expressed by equation (5).
[0076] [ka] (In formula (A), ma1, ma2, na1, and na2 represent average degrees of polymerization, ma1 and ma2 represent 1 to 20, and na1 and na2 represent 0 to 20.) (In formula (B), mb1, mb2, nb1, and nb2 represent average degrees of polymerization, mb1 and mb2 represent 1 to 20, and nb1 and nb2 represent 0 to 20.) (In formula (C), mc1, mc2, nc1, and nc2 represent average degrees of polymerization, mc1 and mc2 represent 1 to 20, and nc1 and nc2 represent 0 to 20.) (In formula (D), md1, md2, nd1, and nd2 represent average degrees of polymerization, md1 and md2 represent 1 to 20, and nd1 and nd2 represent 0 to 20.)
[0077] [ka] (In formula (E), me1, me2, ne1, and ne2 represent average degrees of polymerization, me1 and me2 represent 1 to 20, and ne1 and ne2 represent 0 to 20.) (In formula (F), mf1, mf2, nf1, and nf2 represent average degrees of polymerization, mf1 and mf2 represent 1 to 20, and nf1 and nf2 represent 0 to 20.) (In formula (G), mg1, mg2, ng1, and ng2 represent average degrees of polymerization, mg1 and mg2 represent 1 to 20, and ng1 and ng2 represent 0 to 20.) (In formula (H), mh1, mh2, nh1, and nh2 represent average degrees of polymerization, mh1 and mh2 represent 1 to 20, and nh1 and nh2 represent 0 to 20.)
[0078] [ka] (In formula (I), mi1, mi2, ni1, and ni2 represent average degrees of polymerization, mi1 and mi2 represent 1 to 20, and ni1 and ni2 represent 0 to 20.) (In formula (J), mj1, mj2, nj1, and nj2 represent average degrees of polymerization, mj1 and mj2 represent 1 to 20, and nj1 and nj2 represent 0 to 20.) (In formula (K), mk1, mk2, nk1, and nk2 represent average degrees of polymerization, mk1 and mk2 represent 1 to 20, and nk1 and nk2 represent 0 to 20.) (In formula (L), ml1, ml2, nl1, and nl2 represent average degrees of polymerization, ml1 and ml2 represent 1 to 20, and nl1 and nl2 represent 0 to 20.)
[0079] [ka] (In formula (M), mm1, mm2, nm1, and nm2 represent average degrees of polymerization, mm1 and mm2 represent 1 to 20, and nm1 and nm2 represent 0 to 20.) (In formula (N), mn1, mn2, nn1, and nn2 represent average degrees of polymerization, mn1 and mn2 represent 1 to 20, and nn1 and nn2 represent 0 to 20.) (In formula (O), po1 and po2 each represent an average degree of polymerization, and each represents 1 to 20.) (In formula (P), qp1 and qp2 each represent an average degree of polymerization and are 1 to 10.) In formulas (A) to (P), ma1 to mn1, ma2 to mn2, na1 to nn1, na2 to nn2, po1, po2, qp1, and qp2 may have a range arbitrarily selected from the above-mentioned respective ranges. For example, ma1 to mn1, ma2 to mn2, po1, and po2 may be 1 to 15, 1 to 10, 1 to 8, 1 to 5, or 2 to 3. na1 to nn1 and na2 to nn2 may be 0 to 15, 0 to 10, 0 to 8, 0 to 5, 1 to 6, or 2 to 3. qp1 and qp2 may be 1 to 8, 1 to 5, or 2 to 3.
[0080] The number average molecular weight (Mn) of the fluorine-containing ether compound of this embodiment is preferably in the range of 500 to 10,000, and particularly preferably in the range of 1,000 to 5,000. When the number average molecular weight is 500 or more, the lubricating layer made of the lubricant containing the fluorine-containing ether compound of this embodiment has excellent heat resistance. The number average molecular weight of the fluorine-containing ether compound is more preferably 1,000 or more. In addition, when the number average molecular weight is 10,000 or less, the viscosity of the fluorine-containing ether compound becomes appropriate, and a lubricating layer with a thin film thickness can be easily formed by applying a lubricant containing this. The number average molecular weight of the fluorine-containing ether compound is preferably 5,000 or less, since it has a viscosity that is easy to handle when applied to a lubricant.
[0081] The number average molecular weight (Mn) of the fluorine-containing ether compound is 1 H-NMR and 19 F-NMR, specifically, using the AVANCEIII400 manufactured by Bruker Biospin. 1 H-NMR and 19 This is a value measured by F-NMR. More specifically, 19 The number of repeating units of the PFPE chain is calculated from the integral value measured by F-NMR to determine the number average molecular weight. In the measurement of NMR (nuclear magnetic resonance), the sample is diluted in a hexafluorobenzene / d-acetone (4 / 1 v / v) solvent and measured. 19 The F-NMR chemical shift standard is the hexafluorobenzene peak at -164.7 ppm. 1 The standard for H-NMR chemical shifts is the acetone peak at 2.2 ppm.
[0082] The fluorinated ether compound of this embodiment is preferably subjected to molecular weight fractionation by an appropriate method to make the molecular weight dispersity (ratio of weight average molecular weight (Mw) / number average molecular weight (Mn)) 1.3 or less. In the present embodiment, the method of molecular weight fractionation is not particularly limited, but for example, molecular weight fractionation by silica gel column chromatography, gel permeation chromatography (GPC), or the like, molecular weight fractionation by supercritical extraction, or the like can be used.
[0083] "Manufacturing method" The method for producing the fluorinated ether compound of the present embodiment is not particularly limited, and the compound can be produced by a conventionally known production method. The fluorinated ether compound of the present embodiment can be produced, for example, by the production method shown below.
[0084] (R 3 The two PFPE chains represented by R 1 -R 2 - and R 5 -R 4 - (if and are the same) In formula (1), R 3 The two PFPE chains represented by R 1 -R 2 - and R 5 -R 4 - is the same as (i.e., R 1 and R 5 Same as R 2 and R 4 To prepare a compound in which R 3 A fluorine-based compound is prepared in which a hydroxymethyl group (-CH2OH) is arranged at each end of a perfluoropolyether chain corresponding to the above.
[0085] Next, the hydroxyl group of the hydroxymethyl group located at one end of the fluorine-based compound and R 1 -R 2 - group (=R 5 -R 4 - group) with the epoxy group of an epoxy compound having R 3 At one end of the perfluoropolyether chain corresponding to 1 -R 2 An intermediate compound having a group corresponding to - is obtained.
[0086] R in formula (1) 1 -R 2 - group (=R 5 -R 4 As the epoxy compound having a group which becomes -, for example, compounds represented by the following formulas (6a) to (11a), (6b) to (11b), and (6c) can be used. When the fluorine-based compound is reacted with the epoxy compound to synthesize the intermediate compound, the hydroxyl group of the epoxy compound may be protected with an appropriate protecting group before being reacted with the fluorine-based compound.
[0087] [ka]
[0088] R in formula (1) 1 -R 2 - group (=R 5 -R 4 The epoxy compound having R 1 or R 5 The compound can be produced by reacting an alcohol having a structure corresponding to the terminal group represented by the formula: with epibromohydrin.
[0089] The epoxy compound may be, for example, as shown in the following formula (13): 1 or R 5 Alternatively, the compound may be produced by subjecting an alcohol having a structure corresponding to the terminal group represented by the following formula (I) to an addition reaction with allyl glycidyl ether, and then oxidizing the compound obtained by the addition reaction. The epoxy compound may be, for example, as shown in the following formula (14): 1 or R 5 The copolymer may be produced by reacting an alcohol having a structure corresponding to the terminal group represented by the following formula (I) with glycerin diglycidyl ether. The epoxy compound may be a commercially available product.
[0090] [ka]
[0091] Then, R 3 At one end of the perfluoropolyether chain corresponding to 1 -R 2 - An intermediate compound having a group corresponding to - is reacted with epibromohydrin. By carrying out the above steps, a glycerin structure is formed in the center of the chain structure, and R 3 The two PFPE chains represented by R 1 -R 2 - and R 5 -R 4 A compound in which - is the same as - is obtained.
[0092] (R 1 and R 5 , R 2 and R 4 , R 3 (When one or more of the two PFPE chains shown in In this case, R 3 The two PFPE chains represented by R 1 -R 2 - and R 5 -R 4 In the same manner as in the preparation of the compound in which R 3 At one end of the perfluoropolyether chain corresponding to 1 -R 2 - preparing an intermediate compound having a group corresponding to
[0093] Next, add R to one end. 1 -R 2 - is reacted with epibromohydrin to obtain R 3 At one end of the perfluoropolyether chain corresponding to 1 -R 2A first intermediate compound having a group corresponding to - at the other end and an epoxy group at the other end is prepared.
[0094] Next, add R to one end. 1 -R 2 -R 3 At one end of the perfluoropolyether chain corresponding to 5 -R 4 A second intermediate compound is prepared having a group corresponding to -. Thereafter, the first intermediate compound is reacted with the second intermediate compound. By carrying out the above steps, a glycerin structure is formed in the center of the chain structure, and R 1 and R 5 , R 2 and R 4 , R 3 Compounds can be prepared in which one or more of the two PFPE chains shown in the formula (I) are different.
[0095] The fluorine-containing ether compound of the present embodiment is a compound represented by formula (1), in which a glycerin structure is arranged in the center of a chain structure, and R 3 a PFPE chain represented by the formula: 2 and R 4 and a divalent linking group having a polar group represented by R 1 and R 5 The terminal groups shown in R 1 and R 5 At least one of the terminal groups is an organic group substituted with a cyano group. Therefore, the lubricating layer formed on the protective layer using the lubricant containing the fluorine-containing ether compound of this embodiment has excellent adhesion to the protective layer even if it is thin, and has good chemical resistance and abrasion resistance.
[0096] [Lubricants for magnetic recording media] The lubricant for a magnetic recording medium of this embodiment contains a fluorine-containing ether compound represented by the above formula (1). The lubricant of the present embodiment can be used by mixing, as necessary, known materials used as lubricant materials, so long as the properties resulting from the inclusion of the fluorinated ether compound represented by the above formula (1) are not impaired.
[0097] Specific examples of known materials include FOMBLIN (registered trademark) ZDIAC, FOMBLIN ZDEAL, FOMBLIN AM-2001 (all manufactured by Solvay Solexis), Moresco A20H (manufactured by Moresco), etc. The known material to be mixed with the lubricant of the present embodiment preferably has a number average molecular weight of 1,000 to 10,000.
[0098] When the lubricant of this embodiment contains a material other than the fluorinated ether compound represented by the above formula (1), the content of the fluorinated ether compound represented by the above formula (1) in the lubricant of this embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit can be selected arbitrarily, and may be, for example, 99% by mass or less, 95% by mass or less, 90% by mass or less, or 80% by mass or less.
[0099] Since the lubricant of the present embodiment contains a fluorine-containing ether compound represented by the above formula (1), even if the film thickness is thin, it can cover the surface of the protective layer with a high coverage rate, and form a lubricating layer having excellent chemical resistance and wear resistance.
[0100] [Magnetic recording media] The magnetic recording medium of this embodiment has at least a magnetic layer, a protective layer, and a lubricating layer provided in this order on a substrate. In the magnetic recording medium of this embodiment, one or more underlayers may be provided between the substrate and the magnetic layer as necessary. Also, at least one of an adhesive layer and a soft magnetic layer may be provided between the underlayer and the substrate.
[0101] FIG. 1 is a schematic cross-sectional view showing one embodiment of a magnetic recording medium of the present invention. The magnetic recording medium 10 of this embodiment has a structure in which an adhesive layer 12, a soft magnetic layer 13, a first underlayer 14, a second underlayer 15, a magnetic layer 16, a protective layer 17, and a lubricating layer 18 are sequentially provided on a substrate 11.
[0102] "substrate" The substrate 11 may be, for example, a non-magnetic substrate in which a film made of NiP or a NiP alloy is formed on a base made of a metal or alloy material such as Al or an Al alloy. In addition, the substrate 11 may be a non-magnetic substrate made of a non-metallic material such as glass, ceramics, silicon, silicon carbide, carbon, or resin, or a non-magnetic substrate having a NiP or NiP alloy film formed on a base made of these non-metallic materials.
[0103] Glass substrates are suitable for achieving high recording density because they have rigidity and excellent smoothness. Examples of glass substrates include aluminosilicate glass substrates, and chemically strengthened aluminosilicate glass substrates are particularly suitable. The main surface of the substrate 11 is preferably very smooth with a roughness of Rmax of 6 nm or less and Ra of 0.6 nm or less. Note that the surface roughnesses Rmax and Ra referred to here are based on the JIS B0601 standard.
[0104] "Adhesion layer" The adhesive layer 12 prevents the progress of corrosion of the substrate 11, which occurs when the substrate 11 and the soft magnetic layer 13 provided on the adhesive layer 12 are disposed in contact with each other. The material of the adhesive layer 12 can be appropriately selected from, for example, Cr, a Cr alloy, Ti, a Ti alloy, CrTi, NiAl, an AlRu alloy, etc. The adhesive layer 12 can be formed by, for example, a sputtering method.
[0105] "Soft magnetic layer" The soft magnetic layer 13 preferably has a structure in which a first soft magnetic film, an intermediate layer made of a Ru film, and a second soft magnetic film are laminated in this order. That is, the soft magnetic layer 13 preferably has a structure in which the intermediate layer made of a Ru film is sandwiched between two soft magnetic films, and the soft magnetic films above and below the intermediate layer are anti-ferro-coupling (AFC). The first and second soft magnetic films may be made of a material such as a CoZrTa alloy or a CoFe alloy.
[0106] It is preferable to add any one of Zr, Ta, and Nb to the CoFe alloy used in the first and second soft magnetic films, which promotes the amorphization of the first and second soft magnetic films, improves the orientation of the first underlayer (seed layer), and reduces the flying height of the magnetic head. The soft magnetic layer 13 can be formed by, for example, a sputtering method.
[0107] "First base layer" The first underlayer 14 is a layer for controlling the orientation and crystal size of the second underlayer 15 and the magnetic layer 16 provided thereon. Examples of the first underlayer 14 include a Cr layer, a Ta layer, a Ru layer, or a CrMo alloy layer, a CoW alloy layer, a CrW alloy layer, a CrV alloy layer, and a CrTi alloy layer. The first underlayer 14 can be formed by, for example, a sputtering method.
[0108] "Second base layer" The second underlayer 15 is a layer that controls good orientation of the magnetic layer 16. The second underlayer 15 is preferably a layer made of Ru or a Ru alloy. The second underlayer 15 may be a layer consisting of one layer, or may be composed of multiple layers. When the second underlayer 15 is composed of multiple layers, all the layers may be composed of the same material, or at least one layer may be composed of a different material. The second underlayer 15 can be formed by, for example, a sputtering method.
[0109] "Magnetic layer" The magnetic layer 16 is a magnetic film with an easy axis of magnetization oriented perpendicular or parallel to the substrate surface. The magnetic layer 16 is a layer containing Co and Pt, and may be a layer containing an oxide, Cr, B, Cu, Ta, Zr, etc. to further improve the SNR characteristics. The oxides contained in the magnetic layer 16 include SiO2, SiO, Cr2O3, CoO, Ta2O3, TiO2, and the like.
[0110] The magnetic layer 16 may be composed of a single layer, or may be composed of multiple magnetic layers made of materials with different compositions. For example, when the magnetic layer 16 is composed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, stacked in order from the bottom, the first magnetic layer preferably has a granular structure made of a material containing Co, Cr, and Pt and further containing an oxide. As the oxide contained in the first magnetic layer, for example, oxides of Cr, Si, Ta, Al, Ti, Mg, Co, etc. are preferably used. Among these, TiO2, Cr2O3, SiO2, etc. are particularly preferably used. In addition, the first magnetic layer is preferably made of a composite oxide to which two or more kinds of oxides are added. Among these, Cr2O3-SiO2, Cr2O3-TiO2, SiO2-TiO2, etc. are particularly preferably used.
[0111] The first magnetic layer may contain at least one element selected from the group consisting of B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru and Re, in addition to Co, Cr, Pt and oxides. The second magnetic layer may be made of the same material as the first magnetic layer, and preferably has a granular structure. The third magnetic layer preferably has a non-granular structure made of a material that contains Co, Cr, and Pt and does not contain oxides. The third magnetic layer may contain at least one element selected from the group consisting of B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, Re, and Mn, in addition to Co, Cr, and Pt.
[0112] When the magnetic layer 16 is formed of multiple magnetic layers, it is preferable to provide a nonmagnetic layer between adjacent magnetic layers. When the magnetic layer 16 is formed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, it is preferable to provide a nonmagnetic layer between the first magnetic layer and the second magnetic layer and between the second magnetic layer and the third magnetic layer.
[0113] The non-magnetic layer provided between adjacent magnetic layers in the magnetic layer 16 can suitably be made of, for example, Ru, a Ru alloy, a CoCr alloy, a CoCrX1 alloy (X1 represents at least one element selected from the group consisting of Pt, Ta, Zr, Re, Ru, Cu, Nb, Ni, Mn, Ge, Si, O, N, W, Mo, Ti, V, Zr and B), etc.
[0114] For the non-magnetic layer provided between adjacent magnetic layers of the magnetic layer 16, it is preferable to use an alloy material containing an oxide, a metal nitride, or a metal carbide. Specifically, for example, SiO2, Al2O3, Ta2O5, Cr2O3, MgO, Y2O3, TiO2, etc. can be used as the oxide. For example, AlN, Si3N4, TaN, CrN, etc. can be used as the metal nitride. For example, TaC, BC, SiC, etc. can be used as the metal carbide. The nonmagnetic layer can be formed by, for example, a sputtering method.
[0115] In order to achieve higher recording density, the magnetic layer 16 is preferably a magnetic layer for perpendicular magnetic recording in which the axis of easy magnetization is oriented perpendicular to the substrate surface, but may also be a magnetic layer for in-plane magnetic recording. The magnetic layer 16 may be formed by any known method such as vapor deposition, ion beam sputtering, magnetron sputtering, etc. The magnetic layer 16 is usually formed by sputtering.
[0116] "Protective layer" The protective layer 17 protects the magnetic layer 16. The protective layer 17 may be composed of one layer or multiple layers. A carbon-based protective layer can be preferably used as the protective layer 17, and an amorphous carbon protective layer is particularly preferred. If the protective layer 17 is a carbon-based protective layer, the interaction with the polar group (particularly the hydroxyl group) contained in the fluorine-containing ether compound in the lubricating layer 18 is further enhanced, which is preferable.
[0117] The adhesion between the carbon-based protective layer and the lubricating layer 18 can be controlled by making the carbon-based protective layer hydrogenated carbon and / or nitrogenated carbon and adjusting the hydrogen content and / or nitrogen content in the carbon-based protective layer. The hydrogen content in the carbon-based protective layer is preferably 3 atomic % to 20 atomic % when measured by hydrogen forward scattering (HFS). The nitrogen content in the carbon-based protective layer is preferably 4 atomic % to 15 atomic % when measured by X-ray photoelectron spectroscopy (XPS).
[0118] The hydrogen and / or nitrogen contained in the carbon-based protective layer does not need to be uniformly contained throughout the carbon-based protective layer. The carbon-based protective layer is preferably a compositionally graded layer in which, for example, nitrogen is contained on the lubricating layer 18 side of the protective layer 17, and hydrogen is contained on the magnetic layer 16 side of the protective layer 17. In this case, the adhesion between the magnetic layer 16 and the lubricating layer 18 and the carbon-based protective layer is further improved.
[0119] The thickness of the protective layer 17 is preferably 1 nm to 7 nm. When the thickness of the protective layer 17 is 1 nm or more, sufficient performance as the protective layer 17 can be obtained. When the thickness of the protective layer 17 is 7 nm or less, it is preferable from the viewpoint of making the protective layer 17 thinner.
[0120] The protective layer 17 can be formed by a sputtering method using a target material containing carbon, a CVD (chemical vapor deposition) method using a hydrocarbon raw material such as ethylene or toluene, an IBD (ion beam deposition) method, or the like. When forming a carbon-based protective layer as the protective layer 17, it can be deposited by, for example, a DC magnetron sputtering method. In particular, when forming a carbon-based protective layer as the protective layer 17, it is preferable to deposit an amorphous carbon protective layer by a plasma CVD method. The amorphous carbon protective layer deposited by the plasma CVD method has a uniform surface with small roughness.
[0121] "Lubricating layer" The lubricating layer 18 prevents contamination of the magnetic recording medium 10. In addition, the lubricating layer 18 reduces the frictional force of the magnetic head of the magnetic recording and reproducing device that slides on the magnetic recording medium 10, thereby improving the durability of the magnetic recording medium 10. 1, the lubricating layer 18 is formed on and in contact with the protective layer 17. The lubricating layer 18 is formed by applying the lubricant for magnetic recording media of the above-mentioned embodiment onto the protective layer 17. Thus, the lubricating layer 18 contains the above-mentioned fluorine-containing ether compound.
[0122] When the protective layer 17 disposed below the lubricating layer 18 is a carbon-based protective layer, the lubricating layer 18 is bonded with a high bonding strength to the protective layer 17. As a result, even if the thickness of the lubricating layer 18 is thin, it is easy to obtain a magnetic recording medium 10 in which the surface of the protective layer 17 is covered with a high coverage rate, and contamination of the surface of the magnetic recording medium 10 can be effectively prevented.
[0123] The average thickness of the lubricating layer 18 is preferably 0.5 nm (5 Å) to 2.0 nm (20 Å), and more preferably 0.5 nm (5 Å) to 1.2 nm (12 Å). When the average thickness of the lubricating layer 18 is 0.5 nm or more, the lubricating layer 18 is formed with a uniform thickness without being island-shaped or mesh-shaped. Therefore, the surface of the protective layer 17 can be covered with the lubricating layer 18 with a high coverage. In addition, by setting the average thickness of the lubricating layer 18 to 2.0 nm or less, the lubricating layer 18 can be made sufficiently thin, and the flying height of the magnetic head can be sufficiently reduced.
[0124] "Method of forming lubricating layer" To form the lubricating layer 18, for example, a method can be used in which a magnetic recording medium in the middle of manufacture is prepared in which all layers up to the protective layer 17 are formed on the substrate 11, and a solution for forming a lubricating layer is applied onto the protective layer 17.
[0125] The lubricant layer forming solution can be obtained by dispersing and dissolving the lubricant for magnetic recording media of the above-mentioned embodiment in a solvent as necessary, and adjusting the viscosity and concentration to be suitable for the coating method. Examples of the solvent used in the lubricant layer forming solution include fluorine-based solvents such as Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals).
[0126] The method for applying the solution for forming the lubricating layer is not particularly limited, but examples thereof include spin coating, spraying, paper coating, and dipping. When using the dipping method, for example, the following method can be used. First, the substrate 11 on which each layer up to the protective layer 17 has been formed is immersed in the lubricant layer forming solution placed in the immersion tank of a dip coater. Next, the substrate 11 is lifted from the immersion tank at a predetermined speed. In this way, the lubricant layer forming solution is applied to the surface of the substrate 11 above the protective layer 17. By using the dipping method, the lubricant layer forming solution can be applied uniformly onto the surface of the protective layer 17, and the lubricant layer 18 can be formed on the protective layer 17 with a uniform thickness.
[0127] In this embodiment, it is preferable to perform a heat treatment on the substrate 11 on which the lubricating layer 18 is formed. By performing the heat treatment, the adhesion between the lubricating layer 18 and the protective layer 17 is improved, and the adhesive force between the lubricating layer 18 and the protective layer 17 is improved. The heat treatment temperature is preferably 100°C to 180°C, and more preferably 100°C to 160°C. When the heat treatment temperature is 100°C or higher, the effect of improving the adhesion between the lubricating layer 18 and the protective layer 17 can be sufficiently obtained. Furthermore, by setting the heat treatment temperature to 180°C or lower, thermal decomposition of the lubricating layer 18 can be prevented. The heat treatment time can be appropriately adjusted depending on the heat treatment temperature, and is preferably 10 minutes to 120 minutes.
[0128] In this embodiment, in order to further improve the adhesion of the lubricating layer 18 to the protective layer 17, the lubricating layer 18 may be irradiated with ultraviolet (UV) rays before or after the heat treatment.
[0129] The magnetic recording medium 10 of this embodiment is a substrate 11 on which at least a magnetic layer 16, a protective layer 17, and a lubricating layer 18 are sequentially provided. In the magnetic recording medium 10 of this embodiment, a lubricating layer 18 containing the above-mentioned fluorine-containing ether compound is formed in contact with the protective layer 17. Even if the lubricating layer 18 is thin, it has excellent adhesion, and has good chemical resistance and wear resistance. Therefore, the magnetic recording medium 10 of this embodiment is excellent in reliability, particularly in suppression of silicon contamination, and durability. Therefore, the magnetic recording medium 10 of this embodiment operates stably for a long period of time even in a harsh environment accompanied by a diversification of applications, with a low magnetic head flying height (for example, 10 nm or less). Therefore, the magnetic recording medium 10 of this embodiment is particularly suitable as a magnetic disk to be mounted on a magnetic disk device of the LUL (Load Unload) type. EXAMPLES
[0130] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0131] [Example 1] The compound represented by the above formula (A) was obtained by the method described below. In a 100 mL eggplant flask, add HOCH2CF2O (CF2CF2O) under a nitrogen gas atmosphere. m (CF2O) n 20 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (where m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5), 2.55 g of a compound represented by the above formula (6a), and 20 mL of t-butanol were charged and stirred at room temperature until homogenized to obtain a mixture. 0.90 g of potassium tert-butoxide was added to this mixture, and the mixture was reacted by stirring at 70°C for 16 hours.
[0132] The compound represented by formula (6a) was synthesized by reacting 2-cyanoethanol with epibromohydrin.
[0133] The reaction product obtained after the reaction was cooled to 25°C, transferred to a separatory funnel containing 100mL of water, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the drying agent, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 8.73g of the compound represented by the following formula (15) as an intermediate.
[0134] [ka] (In formula (15), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0135] Next, 5.00 g of the compound represented by formula (15), which is the intermediate obtained above, 0.30 g of epibromohydrin, and 10 mL of t-butanol were charged into a 100 mL recovery flask under a nitrogen gas atmosphere and stirred at room temperature until the mixture became homogeneous. 0.60 g of potassium tert-butoxide was added to this homogeneous liquid and reacted at 70°C for 23 hours with stirring.
[0136] The reaction solution obtained after the reaction was returned to room temperature, 5 g of 10% hydrogen chloride-methanol solution (hydrogen chloride-methanol reagent (5-10%), Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at room temperature for 4 hours. The reaction solution was then transferred little by little to a separatory funnel containing 100 mL of saline, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline, in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 4.20 g of compound (A) (in formula (A), ma1, ma2, na1, and na2, which indicate the average degree of polymerization, are 4.5).
[0137] The obtained compound (A) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(19H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0138] [Example 2] The compound represented by the above formula (B) was obtained by the method described below. The compound represented by the above formula (15) was reacted with epibromohydrin to obtain a compound represented by the following formula (16) as an intermediate.
[0139] [ka] (In formula (16), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0140] In a 100 mL eggplant flask, add HOCH2CF2O (CF2CF2O) under a nitrogen gas atmosphere. m (CF2O) n 20 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (in the formula, m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5), 5.70 g of a compound represented by the following formula (6ba), and 20 mL of t-butanol were charged and stirred at room temperature until homogenized to obtain a mixture. 0.90 g of potassium tert-butoxide was added to this mixture, and the mixture was reacted by stirring at 70°C for 16 hours.
[0141] [ka] (In formula (6ba), THP represents a tetrahydropyranyl group.)
[0142] The compound represented by formula (6ba) was synthesized by the following method. First, a compound having a cyano group and a hydroxyl group was synthesized by addition reaction of 2-cyanoethanol with allyl glycidyl ether. Then, the secondary hydroxyl group of the synthesized compound having a cyano group and a hydroxyl group was protected with dihydropyran, and the double bond was oxidized to obtain an epoxy compound having a cyano group represented by formula (6ba).
[0143] The reaction product obtained after the reaction was cooled to 25°C, transferred to a separatory funnel containing 100mL of water, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the drying agent, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 17.5g of the compound represented by the following formula (17) as an intermediate.
[0144] [ka] (In formula (17), m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5. THP represents a tetrahydropyranyl group.)
[0145] Next, 10.0 g of the compound represented by the above formula (16), 10.2 g of the compound represented by the above formula (17), and 20 mL of t-butanol were charged into a 100 mL recovery flask under a nitrogen gas atmosphere and stirred at room temperature until the mixture became homogeneous. 0.3 g of potassium tert-butoxide was added to this homogeneous liquid and reacted with stirring at 70°C for 22 hours.
[0146] The reaction solution obtained after the reaction was returned to room temperature, 20 g of 10% hydrogen chloride-methanol solution (hydrogen chloride-methanol reagent (5-10%), Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at room temperature for 4 hours. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline solution, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline solution, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline solution, in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 13.5 g of compound (B) (in formula (B), mb1, mb2, nb1, and nb2, which indicate the average degree of polymerization, are 4.5).
[0147] The obtained compound (B) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(24H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0148] [Example 3] The compound represented by the above formula (C) was obtained by the method described below. The same operation as in Example 2 was performed except that the compound represented by formula (6ca) was used instead of the compound represented by formula (6ba) in Example 2, to obtain 8.5 g of compound (C) (in formula (C), mc1, mc2, nc1, and nc2, which indicate the average polymerization degree, are 4.5).
[0149] [ka] (In formula (6ca), THP represents a tetrahydropyranyl group.)
[0150] The compound represented by formula (6ca) was synthesized by protecting the secondary hydroxyl group of glycerin diglycidyl ether with dihydropyran, followed by monoaddition reaction of 2-cyanoethanol.
[0151] The obtained compound (C) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0152] [Example 4] The compound represented by the above formula (D) was obtained by the method described below. The same procedure as in Example 2 was carried out except that epibromohydrin was used instead of the compound represented by formula (16) in Example 2, to obtain 5.6 g of compound (D) (in formula (D), md1, md2, nd1, and nd2, which indicate the average polymerization degrees, are 4.5).
[0153] The obtained compound (D) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0154] [Example 5] The compound represented by the above formula (E) was obtained by the method described below. The compound represented by the above formula (17) was reacted with epibromohydrin to obtain a compound represented by the following formula (18) as an intermediate.
[0155] [ka] (In formula (18), m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5. THP represents a tetrahydropyranyl group.)
[0156] The same operations as in Example 2 were carried out except that the compound represented by formula (18) was used instead of the compound represented by formula (16) in Example 2, and the compound represented by formula (6ca) was used instead of the compound represented by formula (6ba), to obtain 6.2 g of compound (E) (in formula (E), me1, me2, ne1, and ne2, which indicate the average degree of polymerization, are 4.5).
[0157] The obtained compound (E) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(34H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0158] [Example 6] The compound represented by the above formula (F) was obtained by the method described below. The same operation as in Example 1 was performed except that the compound represented by formula (8ba) was used instead of the compound represented by formula (6a) in Example 1, to obtain 5.1 g of compound (F) (in formula (F), mf1, mf2, nf1, and nf2, which indicate the average degree of polymerization, are 4.5).
[0159] [ka] (In formula (8ba), THP represents a tetrahydropyranyl group.)
[0160] The compound represented by formula (8ba) was synthesized by the following method. First, a compound having a cyano group and a hydroxyl group was synthesized by addition reaction of 3-hydroxybutyronitrile with allyl glycidyl ether. Then, the secondary hydroxyl group of the synthesized compound having a cyano group and a hydroxyl group was protected with dihydropyran, and the double bond was oxidized to obtain an epoxy compound having a cyano group represented by formula (8ba).
[0161] The obtained compound (F) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=1.50(6H), 3.40-3.60(4H), 3.65-3.85(6H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0162] [Example 7] The compound represented by the above formula (G) was obtained by the method described below. The same operation as in Example 1 was performed except that the compound represented by formula (9ba) was used instead of the compound represented by formula (6a) in Example 1, to obtain 4.9 g of compound (G) (in formula (G), mg1, mg2, ng1, and ng2, which indicate the average polymerization degree, are 4.5).
[0163] [ka] (In formula (9ba), THP represents a tetrahydropyranyl group.)
[0164] The compound represented by formula (9ba) was synthesized by the following method. First, a compound having a cyano group and a hydroxyl group was synthesized by addition reaction of 3-hydroxyglutaronitrile with allyl glycidyl ether. Then, the secondary hydroxyl group of the synthesized compound having a cyano group and a hydroxyl group was protected using dihydropyran, and the double bond was oxidized to obtain an epoxy compound having a cyano group represented by formula (9ba).
[0165] The obtained compound (G) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(8H), 3.65-3.85(6H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0166] [Example 8] The compound represented by the above formula (H) was obtained by the method described below. The same procedure as in Example 1 was carried out except that the compound represented by the above formula (7a) was used instead of the compound represented by the formula (6a) in Example 1, thereby obtaining 5.3 g of compound (H) (in formula (H), mh1, mh2, nh1, and nh2, which indicate the average degree of polymerization, are 4.5).
[0167] The compound represented by formula (7a) used in the reaction was synthesized by oxidizing allyl cyanoacetate with metachloroperbenzoic acid.
[0168] The obtained compound (H) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.75-4.10(23H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0169] [Example 9] The compound represented by the above formula (I) was obtained by the method described below. The same procedure as in Example 1 was carried out except that the compound represented by formula (10ba) was used instead of the compound represented by formula (6a) in Example 1, thereby obtaining 5.2 g of compound (I) (in formula (I), mi1, mi2, ni1, and ni2, which indicate the average degree of polymerization, are 4.5).
[0170] [ka] (In formula (10ba), MOM represents a methoxymethyl group.)
[0171] The compound represented by formula (10ba) was synthesized by the following method. First, a compound having a cyano group and a hydroxyl group was synthesized by addition reaction of 2-cyanophenol with allyl glycidyl ether. Then, the secondary hydroxyl group of the synthesized compound having a cyano group and a hydroxyl group was protected by using chloromethyl methyl ether, and the double bond was oxidized to obtain an epoxy compound having a cyano group represented by formula (10ba).
[0172] The obtained compound (I) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.60-3.90(25H), 4.00-4.10(8H), 7.00-7.50(8H) 19F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0173] [Example 10] The compound represented by the above formula (J) was obtained by the method shown below. The same procedure as in Example 5 was carried out except that the compound represented by the above formula (9ba) was used instead of the compound represented by the formula (6ca) in Example 5, thereby obtaining 5.0 g of compound (J) (in formula (J), mj1, mj2, nj1, and nj2, which indicate the average degree of polymerization, are 4.5).
[0174] The obtained compound (J) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(6H), 3.65-3.85(7H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0175] [Example 11] The compound represented by the above formula (K) was obtained by the method described below. The same procedure as in Example 5 was carried out except that the compound represented by the above formula (10a) was used instead of the compound represented by the formula (6ca) in Example 5, to obtain 6.5 g of compound (K) (in formula (K), mk1, mk2, nk1, and nk2, which indicate the average polymerization degree, are 4.5).
[0176] The obtained compound (K) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1H-NMR (acetone-D6): δ[ppm]=3.40-3.60(2H), 3.60-3.90(22H), 4.00-4.10(8H), 7.00-7.50(4H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0177] [Example 12] The compound represented by the above formula (L) was obtained by the method described below. The same procedure as in Example 5 was carried out except that the compound represented by formula (19) was used instead of the compound represented by formula (6ca) in Example 5, to obtain 5.5 g of compound (L) (in formula (L), ml1, ml2, nl1, and nl2, which indicate the average degree of polymerization, are 4.5).
[0178] [ka] (In formula (19), THP represents a tetrahydropyranyl group.)
[0179] The compound represented by formula (19) was synthesized by the following method: The secondary hydroxyl group of glycerin diallyl ether was protected with dihydropyran, and one of the double bonds was oxidized to obtain an epoxy compound having an allyl group represented by formula (19).
[0180] The obtained compound (L) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.10(2H), 3.40-3.60(4H), 3.65-3.85(25H), 3.85-4.10(8H), 6.90(2H), 7.25(1H) 19F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0181] [Example 13] The compound represented by the above formula (M) was obtained by the method described below. The same procedure as in Example 5 was carried out except that the compound represented by formula (20) was used instead of the compound represented by formula (6ca) in Example 5, to obtain 4.5 g of compound (M) (in formula (M), mm1, mm2, nm1, and nm2, which indicate the average polymerization degree, are 4.5).
[0182] [ka]
[0183] The compound represented by formula (20) was synthesized by the following method: a compound having a phenyl group was synthesized by addition reaction of phenol with allyl glycidyl ether, and the double bond was oxidized to obtain an epoxy compound having a phenyl group represented by formula (20).
[0184] The obtained compound (M) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(2H), 3.60-3.90(27H), 4.00-4.10(8H), 6.90(5H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0185] [Example 14] The compound represented by the above formula (N) was obtained by the method described below. The same procedure as in Example 5 was carried out except that the compound represented by formula (21) was used instead of the compound represented by formula (6ca) in Example 5, to obtain 4.2 g of compound (N) (in formula (N), mn1, mn2, nn1, and nn2, which indicate the average degree of polymerization, are 4.5).
[0186] [ka] (In formula (21), MOM represents a methoxymethyl group.)
[0187] The compound represented by formula (21) was synthesized by the method shown below. A compound was synthesized by reacting 2-thiopheneethanol with epibromohydrin, and the obtained compound was hydrolyzed. The primary hydroxyl group of the obtained hydrolyzate was protected with a t-butyldimethylsilyl group, and the secondary hydroxyl group was protected with a methoxymethyl group. The t-butyldimethylsilyl group was deprotected from the obtained compound, and the generated primary hydroxyl group was reacted with epibromohydrin to obtain an epoxy compound having a thienylethyl group represented by formula (21).
[0188] The obtained compound (N) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.10(2H), 3.40-3.60(4H), 3.65-3.85(28H), 3.85-4.10(7H), 6.90(2H), 7.25(1H) 19 F-NMR (acetone-D6): δ[ppm]=-55.5~-51.5(18F), -78.5(4F), -80.5(4F), -91.0~-88.5(36F)
[0189] [Example 15] The compound represented by the above formula (D) was obtained by the method described below. HOCH2CF2O(CF2CF2O) of Example 1 m (CF2O) nInstead of a compound represented by CF2CH2OH (where m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5), which has a number average molecular weight of 1000 and a molecular weight distribution of 1.1, HOCH2CF2O(CF2CF2O) md (CF2O) nd The same operations as in Example 1 were carried out except that a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (in the formula, md indicating the average degree of polymerization is 7.0, and nd indicating the average degree of polymerization is 0) was used, and a compound represented by the above formula (6ba) was used instead of the compound represented by the above formula (6a), to obtain 8.5 g of compound (D) (in formula (D), md1 and md2 indicating the average degrees of polymerization are 7.0, and nd1 and nd2 indicating the average degrees of polymerization are 0).
[0190] The obtained compound (D) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-78.5(4F), -81.3(4F), -90.0~-88.5(56F)
[0191] [Example 16] The compound represented by the above formula (O) was obtained by the method described below. HOCH2CF2O(CF2CF2O) of Example 1 m (CF2O) n Instead of the compound represented by CF2CH2OH, HOCH2CF2CF2O (CF2CF2CF2O) pThe same operations as in Example 1 were carried out except that a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CF2CH2OH (in the formula, p indicating the average degree of polymerization is 4.5) was used, and a compound represented by the above formula (6ba) was used instead of the compound represented by the above formula (6a), to obtain 3.4 g of compound (O) (in formula (O), po1 and po2 indicate the average degrees of polymerization, each of which is 4.5).
[0192] The obtained compound (O) 1 H-NMR and 19 F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-84.0~-83.0(36F), -86.4(8F), -124.3(8F), -130.0~-129.0(18F)
[0193] [Example 17] The compound represented by the above formula (P) was obtained by the method described below. HOCH2CF2O(CF2CF2O) of Example 1 m (CF2O) n Instead of the compound represented by CF2CH2OH, HOCH2CF2CF2CF2O (CF2CF2CF2CF2O) q The same operations as in Example 1 were carried out except that a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CF2CF2CH2OH (in the formula, q indicating the average degree of polymerization is 3.0) was used, and a compound represented by the above formula (6ba) was used instead of the compound represented by the above formula (6a), to obtain 3.3 g of compound (P) (in formula (P), qp1 and qp2 indicate the average degrees of polymerization, each of which is 3.0).
[0194] The obtained compound (P) 1 H-NMR and 19F-NMR measurement was performed, and the structure was identified based on the following results. 1 H-NMR (acetone-D6): δ[ppm]=3.40-3.60(4H), 3.65-3.85(8H), 3.85-4.10(29H) 19 F-NMR (acetone-D6): δ[ppm]=-84.0~-83.0(32F), -122.5(8F), -126.0(24F), -129.0~-128.0(8F)
[0195] The compounds of Examples 1 to 17 thus obtained are represented by the formula (1) 1 The structure of R 2 (a in formula (2-1)), R 3 (b and c in formula (3), d in formula (4), and e in formula (5)), R 4 (a in formula (2-1)), R 5 The structures of the compounds are shown in Table 1. 2 and R 4 Y in the above formula (2-1) represents 2 is -O-. Also, R 2 and R 4 In the formula (2-1) where a is 1 or 2, any compound represented by Y 1 is -O-.
[0196] [Table 1]
[0197] [Comparative Example 1] [Comparative Example 2] The compound represented by the following formula (V) was synthesized by the method described in Patent Document 1.
[0198] [ka] (In formula (V), mv1 and mv2, which indicate the average degree of polymerization, are 7.0.)
[0199] [Comparative Example 3] [Comparative Example 4] The compound represented by the following formula (W) was synthesized by the method described in Patent Document 2.
[0200] [ka] (In formula (W), mw1, mw2, nw1, and nw2, which indicate the average degree of polymerization, are 4.5.)
[0201] [Comparative Example 5] [Comparative Example 6] The compound represented by the following formula (X) was synthesized by the method described in Patent Document 3.
[0202] [ka] (In formula (X), mx and nx, which indicate the average degree of polymerization, are 10.0.)
[0203] [Comparative Example 7] [Comparative Example 8] The compound represented by the following formula (Y) was synthesized by the method described in Patent Document 3.
[0204] [ka] (In formula (Y), my and ny, which indicate the average degree of polymerization, are 10.0.)
[0205] [Comparative Example 9] The compound represented by the following formula (Z) was synthesized by the method described in Patent Document 2.
[0206] [ka] (In formula (Z), mz and nz, which indicate the average degree of polymerization, are 10.0.)
[0207] Next, a lubricant layer-forming solution was prepared using the compounds obtained in Examples 1 to 17 and Comparative Examples 1 to 9 by the method described below. Then, using the obtained lubricant layer-forming solution, a lubricant layer of a magnetic recording medium was formed by the method described below, and the magnetic recording media of Examples 1 to 17 and Comparative Examples 1 to 9 were obtained.
[0208] "Lubricant layer forming solution" The compounds obtained in Examples 1 to 17 and Comparative Examples 1 to 9 were each dissolved in a fluorine-based solvent, Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals Co., Ltd.), and diluted with Vertrel XF so that the film thickness when applied onto the protective layer would be 9.0 Å to 9.5 Å, to prepare a solution for forming a lubricating layer.
[0209] "Magnetic recording media" A magnetic recording medium was prepared by sequentially providing an adhesive layer, a soft magnetic layer, a first underlayer, a second underlayer, a magnetic layer, and a protective layer on a substrate having a diameter of 65 mm. The protective layer was made of carbon. On the protective layer of the magnetic recording medium on which each layer up to the protective layer had been formed, the lubricant layer forming solutions of Examples 1 to 17 and Comparative Examples 1 to 9 were applied by dipping. The dipping was performed under the conditions of an immersion speed of 10 mm / sec, an immersion time of 30 sec, and a pull-up speed of 1.2 mm / sec. The magnetic recording medium coated with the lubricant layer-forming solution was then placed in a thermostatic bath, and a heat treatment to remove the solvent in the lubricant layer-forming solution and improve the adhesion between the protective layer and the lubricant layer was performed for 10 minutes at the thermostatic bath temperature (heat treatment temperature) shown in Table 2, thereby forming a lubricant layer on the protective layer and obtaining a magnetic recording medium.
[0210] The thickness of the lubricating layer of each of the magnetic recording media thus obtained in Examples 1 to 17 and Comparative Examples 1 to 9 was measured using an FT-IR (product name: Nicolet iS50, manufactured by Thermo Fisher Scientific Co.) The results are shown in Table 2.
[0211] [Table 2]
[0212] Table 2 also shows the number average molecular weights (Mn) of the compounds of Examples 1 to 17 and Comparative Examples 1 to 9.
[0213] (Measurement of adhesion (bond ratio) between lubricating layer and protective layer) The magnetic recording medium with the lubricating layer formed thereon was immersed in a solvent, Vertrel XF, for 10 minutes and then pulled up for cleaning. The magnetic recording medium was immersed in the solvent at a speed of 10 mm / sec and pulled up at a speed of 1.2 mm / sec. Thereafter, the thickness of the lubricating layer was measured in the same manner as in the measurement of the thickness of the lubricating layer before cleaning.
[0214] The thickness of the lubricant layer before cleaning was designated A, and the thickness of the lubricant layer after cleaning (solvent immersion) was designated B. The bond rate of the lubricant was calculated from the ratio of A to B ((B / A) x 100(%)). The results are shown in Table 2.
[0215] Further, the magnetic recording media of Examples 1 to 17 and Comparative Examples 1 to 9 were subjected to the following wear resistance test and chemical resistance test. (Wear resistance test) Using a pin-on-disk type friction and wear tester, an alumina ball with a diameter of 2 mm was slid as a contact on the lubricating layer of the magnetic recording medium at a load of 40 gf and a sliding speed of 0.25 m / sec to measure the friction coefficient of the surface of the lubricating layer. The sliding time until the friction coefficient of the surface of the lubricating layer suddenly increased was then measured. The sliding time until the friction coefficient suddenly increased was measured four times for the lubricating layer of each magnetic recording medium, and the average value (time) was used as an index of the wear resistance of the lubricant coating.
[0216] The results for the magnetic recording media using the compounds of Examples 1 to 17 and the compounds of Comparative Examples 1 to 9 are shown in Table 2. The wear resistance was evaluated based on the sliding time until the coefficient of friction suddenly increased, as follows. ◎(Excellent): 650sec or more ○(Good): 550 sec or more, less than 650 sec △ (OK): 450 sec or more, less than 550 sec × (Not acceptable): Less than 450 seconds
[0217] The time until the friction coefficient increases sharply can be used as an index of the wear resistance of the lubricating layer for the following reason. The lubricating layer of the magnetic recording medium wears away as the magnetic recording medium is used, and when the lubricating layer is worn away, the contact and the protective layer come into direct contact, causing a sharp increase in the friction coefficient. The time until the friction coefficient increases sharply is thought to be correlated with the friction test.
[0218] (Chemical Resistance Test) The contamination of magnetic recording media by environmental substances that generate contaminants in a high-temperature environment was investigated using the method described below. Si ions were used as the environmental substances, and the amount of Si adsorption was measured as the amount of contaminants that contaminate the magnetic recording media generated by the environmental substances.
[0219] Specifically, the magnetic recording medium to be evaluated was kept in the presence of siloxane-based Si rubber for 240 hours in a high-temperature environment of 85°C and 0% humidity. The amount of Si adsorption on the surface of the magnetic recording medium was then analyzed and measured using secondary ion mass spectrometry (SIMS), and the degree of contamination by Si ions was evaluated as the amount of Si adsorption. The amount of Si adsorption was evaluated using a numerical value when the result of Comparative Example 1 was set to 1.00. The results are shown in Table 2.
[0220] A comprehensive evaluation was then carried out on the magnetic recording media of Examples 1 to 17 and Comparative Examples 1 to 9 based on the following criteria. The results are shown in Table 2. ◎ (Excellent): The time until the friction coefficient suddenly increases is 650 seconds or more, and the amount of Si adsorption is less than 0.90 ○ (Good): The time until the friction coefficient suddenly increases is 550 seconds or more and less than 650 seconds, and the amount of Si adsorption is 0.90 or more and less than 1.00. △ (Acceptable): The time until the friction coefficient increases sharply is between 450 and 650 seconds, and the amount of Si adsorption is between 1.00 and 1.40. × (Not acceptable): The time until the friction coefficient suddenly increases is less than 450 seconds, and the amount of Si adsorption is 1.40 or more.
[0221] As shown in Table 2, the magnetic recording media of Examples 1 to 17 all had a bond ratio of 60% or more and were rated as excellent (excellent). This confirmed that the lubricating layers of the magnetic recording media of Examples 1 to 17 had excellent adhesion despite their thin thickness, and also had good chemical resistance and wear resistance.
[0222] In particular, R in formula (1) 2 and R 4 The total number of hydroxyl groups in the structure of R is 4. 1 and R 5 In Examples 3, 4, 6, and 7, a compound in which R in formula (1) is any one of formula (6-1), formula (8), and formula (9) is used, 2 and R 4 The total number of hydroxyl groups in the structure of R is 4. 1 is the formula (6-1), and R 5 In Examples 10 and 14, which used a compound represented by formula (9) or a thienylethyl group, the bond ratio was 70%, the amount of Si adsorption was 0.64 or less, and the adhesion and chemical resistance were good.
[0223] R 2 and R 4 The total number of hydroxyl groups in the structure of R is 4. 2 and R 4 Example 4, which uses compound (D) having the same number of hydroxyl groups in the structure of R, has a symmetrical structure with the glycerin structure at the center. Therefore, Example 4 is easy to spread evenly on the protective layer, and R 2 and R 4 It is presumed that, compared to Example 3, which used compound (C) having a different number of hydroxyl groups in the structure of R, the coating property was improved and excellent chemical resistance was obtained. 2 and R 4The chemical resistance was better than that of Example 5, which used compound (E) in which the total number of hydroxyl groups contained in the structure was 5. This is presumably because, in Example 4, the number of polar groups not involved in the bond between the lubricating layer and the active sites on the protective layer was smaller than that of Example 5, and the polar groups not involved in the bond between the lubricating layer and the active sites on the protective layer were suppressed from attracting environmental substances that generate pollutants.
[0224] In addition, from the results of Examples 1 to 3, R 2 and R 4 It was confirmed that the more hydroxyl groups contained in the structure of the compound, the higher the bond rate and the better the adhesion, and the lower the amount of silicon adsorbed and the better the chemical resistance. 2 and R 4 In Example 5, which used a compound with a total number of hydroxyl groups in the structure of 5, the bond rate was higher than in Example 4, which used a compound with a total number of 4, but the amount of Si adsorption was greater. This is presumably because the hydroxyl groups in the compound that are not involved in bonding with the active sites on the protective layer attracted environmental substances that generate pollutants to the lubricating layer.
[0225] In contrast, in Comparative Examples 1 and 3, which used a compound in which a glycerin structure was arranged in the center of a chain structure, and a perfluoropolyether chain and an end group having two hydroxyl groups were bonded to both sides of the chain structure in that order, with hydroxyl groups arranged at both extreme ends of the chain structure, the bond rate was 80%, and the adhesion was higher than in Examples 1 to 17. However, in Comparative Examples 1 and 3, the adhesion was too strong, which impaired the lubricity of the lubricating layer, and the results of the wear resistance test were "Fair (good)".
[0226] In Comparative Examples 2 and 4, in which the same compounds as those in Comparative Examples 1 and 3 were used, respectively, but the heat treatment temperature (temperature of the thermostatic bath) was lowered to weaken the adhesion, the results of the wear resistance test were "○ (good)", but the amount of Si adsorption was large. This is presumably because the hydroxyl groups in the compounds that are not involved in bonding with the active sites on the protective layer attracted environmental substances that generate pollutants to the lubricating layer.
[0227] In addition, in Comparative Example 5, which used a compound in which a perfluoropolyether chain was arranged in the center of a chain structure, terminal groups having one hydroxyl group and one cyano group at both ends, and a cyano group was arranged at the extreme ends of both ends of the chain structure, the bond rate was 50%, and the adhesion was lower and the amount of Si adsorption was higher than in Examples 1 to 17.
[0228] In addition, in Comparative Example 7, which used a compound in which a perfluoropolyether chain was arranged in the center of a chain structure, an end group having two hydroxyl groups was arranged at one end, and an end group having one hydroxyl group and one cyano group was arranged at the other end, and a hydroxyl group was arranged at the extreme end of one of the chain structures and a cyano group was arranged at the extreme end of the other, the bond ratio was 55%, and the adhesion was lower and the Si adsorption amount was higher than in Examples 1 to 17.
[0229] This is presumably because the compounds used in Comparative Examples 5 and 7 did not have a glycerin structure in the center of the chain structure, and therefore the adhesion-improving effect due to the bond between the hydroxyl group located in the center of the chain structure and the protective layer was not obtained. In addition, in Comparative Examples 6 and 8, which used the same compounds as Comparative Examples 5 and 7, respectively, but strengthened adhesion by increasing the heat treatment temperature (constant temperature bath temperature), the bond rate was 60% or more, but the result of the abrasion resistance test was "△ (passable)."
[0230] In addition, in Comparative Example 9, which used a compound in which a perfluoropolyether chain was arranged in the center of a chain structure, terminal groups having two hydroxyl groups were bonded to both sides of the chain structure, and a hydroxyl group was arranged at each of the extreme ends of the chain structure, the result of the abrasion resistance test was "× (fail)", and the amount of Si adsorption was greater than those of Examples 1 to 17. [Industrial Applicability]
[0231] By using a lubricant for magnetic recording media containing the fluorinated ether compound of the present invention, it is possible to form a lubricating layer which has excellent adhesion even when thin, and which has good resistance to chemicals and abrasion resistance. [Explanation of symbols]
[0232] 10. Magnetic recording media 11... Substrate 12. Adhesion layer 13...Soft magnetic layer 14...1st base layer 15...Second base layer 16...magnetic layer 17...protective layer 18...Lubricating layer
Claims
1. A fluorine-containing ether compound represented by the following formula (1): R 1 -R 2 -CH 2 -R 3 -CH 2 -OCH 2 CH(OH)CH 2 O-CH 2 -R 3 -CH 2 -R 4 -R 5 (1) (In formula (1), R 3 is any one selected from the perfluoropolyether chains represented by the following formulas (3) to (5); R 2 and R 4 are divalent linking groups represented by the following formula (2-1), which may be the same or different; R 1 and R 5 is R 2 Or R 4 are terminal groups bonded to oxygen atoms of 1 and R 5 is a phenyl group or an organic group having 1 to 5 carbon atoms, which is substituted with at least one cyano group. -O-X-(Y 1 X) a -Y 2 - (2-1) (In formula (2-1), a represents an integer of 0 to 2; X is represented by the following formula (2); Y 1 represents any one selected from —O—, —CH 2 —, —CH 2 O—, and —OCH 2 —; and Y 2 represents —O— or —CH 2 O—.) -CH2CH(OH)CH2- (2) -CF 2 -(OCF 2 CF 2 ) b -(OCF 2 ) c -OCF 2 - (3) (In formula (3), b and c represent the average degree of polymerization, b represents 1 to 20, and c represents 0 to 20.) -CF 2 CF 2 - (OCF 2 CF 2 CF 2 ) d -OCF 2 CF 2 - (4) (In formula (4), d represents the average degree of polymerization and is 1 to 20.) -CF 2 CF 2 CF 2 - (OCF 2 CF 2 CF 2 CF 2 ) e -OCF 2 CF 2 CF 2 - (5) (In formula (5), e represents the average degree of polymerization and is 1 to 10.)
2. A fluorine-containing ether compound represented by the following formula (1): R 1 -R 2 -CH 2 -R 3 -CH 2 -OCH 2 CH(OH)CH 2 O-CH 2 -R 3 -CH 2 -R 4 -R 5 (1) (In formula (1), R 3 is any one selected from the perfluoropolyether chains represented by the following formulas (3) to (5); R 2 and R 4 are divalent linking groups represented by the following formula (2-1), which may be the same or different; R 1 and R 5 is R 2 Or R 4 and may be the same or different; one of R 1 and R 5 is a phenyl group or an alkyl group having 1 to 5 carbon atoms substituted with at least one cyano group, and the other is an organic group having at least one group containing an aromatic hydrocarbon, a group containing an aromatic heterocycle, an alkenyl group, or an alkynyl group. -O-X-(Y 1 X) a -Y 2 - (2-1) (In formula (2-1), a represents an integer of 0 to 2; X is represented by the following formula (2); Y 1 represents any one selected from —O—, —CH 2 —, —CH 2 O—, and —OCH 2 —; and Y 2 represents —O— or —CH 2 O—.) -CH2CH(OH)CH2- (2) -CF 2 -(OCF 2 CF 2 ) b -(OCF 2 ) c -OCF 2 - (3) (In formula (3), b and c represent the average degree of polymerization, b represents 1 to 20, and c represents 0 to 20.) -CF 2 CF 2 - (OCF 2 CF 2 CF 2 ) d -OCF 2 CF 2 - (4) (In formula (4), d represents the average degree of polymerization and is 1 to 20.) -CF 2 CF 2 CF 2 - (OCF 2 CF 2 CF 2 CF 2 ) e -OCF 2 CF 2 CF 2 - (5) (In formula (5), e represents the average degree of polymerization and is 1 to 10.) 2 CF 2 CF 2 - (5) (In formula (5), e represents the average degree of polymerization and is 1 to 10.)
3. R in the formula (1) 2 and the hydroxyl group contained in R 4 The fluorine-containing ether compound according to claim 1 or 2, wherein the total number of hydroxyl groups contained in
4. Y in the formula (2-1) 1 and Y 2 The fluorine-containing ether compound according to claim 1 or 2, wherein: is -O-.
5. In the formula (1), R 3 The two perfluoropolyether chains represented by R 2 and R 4 are the same, and R 1 and R 5 The fluorine-containing ether compound according to claim 1 or 2, wherein
6. A fluorine-containing ether compound which is any of compounds represented by the following formulas (A) to (P): 【Chemistry 1】 (In formula (A), ma1, ma2, na1, and na2 represent average degrees of polymerization, ma1 and ma2 represent 1 to 20, and na1 and na2 represent 0 to 20.) (In formula (B), mb1, mb2, nb1, and nb2 represent average degrees of polymerization, mb1 and mb2 represent 1 to 20, and nb1 and nb2 represent 0 to 20.) (In formula (C), mc1, mc2, nc1, and nc2 represent average degrees of polymerization, mc1 and mc2 represent 1 to 20, and nc1 and nc2 represent 0 to 20.) (In formula (D), md1, md2, nd1, and nd2 represent average degrees of polymerization, md1 and md2 represent 1 to 20, and nd1 and nd2 represent 0 to 20.) 【Chemistry 2】 (In formula (E), me1, me2, ne1, and ne2 represent average degrees of polymerization, me1 and me2 represent 1 to 20, and ne1 and ne2 represent 0 to 20.) (In formula (F), mf1, mf2, nf1, and nf2 represent average degrees of polymerization, mf1 and mf2 represent 1 to 20, and nf1 and nf2 represent 0 to 20.) (In formula (G), mg1, mg2, ng1, and ng2 represent average degrees of polymerization, mg1 and mg2 represent 1 to 20, and ng1 and ng2 represent 0 to 20.) (In formula (H), mh1, mh2, nh1, and nh2 represent average degrees of polymerization, mh1 and mh2 represent 1 to 20, and nh1 and nh2 represent 0 to 20.) 【Chemistry 3】 (In formula (I), mi1, mi2, ni1, and ni2 represent average degrees of polymerization, mi1 and mi2 represent 1 to 20, and ni1 and ni2 represent 0 to 20.) (In formula (J), mj1, mj2, nj1, and nj2 represent average degrees of polymerization, mj1 and mj2 represent 1 to 20, and nj1 and nj2 represent 0 to 20.) (In formula (K), mk1, mk2, nk1, and nk2 represent average degrees of polymerization, mk1 and mk2 represent 1 to 20, and nk1 and nk2 represent 0 to 20.) (In formula (L), ml1, ml2, nl1, and nl2 represent average degrees of polymerization, ml1 and ml2 represent 1 to 20, and nl1 and nl2 represent 0 to 20.) 【Chemistry 4】 (In formula (M), mm1, mm2, nm1, and nm2 represent average degrees of polymerization, mm1 and mm2 represent 1 to 20, and nm1 and nm2 represent 0 to 20.) (In formula (N), mn1, mn2, nn1, and nn2 represent average degrees of polymerization, mn1 and mn2 represent 1 to 20, and nn1 and nn2 represent 0 to 20.) (In formula (O), po1 and po2 each represent an average degree of polymerization, and each represents 1 to 20.) (In formula (P), qp1 and qp2 each represent an average degree of polymerization, and each represents 1 to 10.)
7. A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of claims 1 to 6.
8. A magnetic recording medium having at least a magnetic layer, a protective layer, and a lubricating layer sequentially provided on a substrate, 7. A magnetic recording medium, comprising the lubricating layer comprising the fluorine-containing ether compound according to claim 1.
9. 9. The magnetic recording medium according to claim 8, wherein the average thickness of the lubricating layer is from 0.5 nm to 2.0 nm.
Citation Information
Patent Citations
Preparation method for perfluoronitrile vinyl ether
CN102320992A
JP1972006168U
Unsaturated perfluoronitrile compound and its production
JP1996134036A
Perfluoropolyether compound and lubricating agent comprising the same
JP2011093981A
Fluorine-containing ether compound, lubricant for magnetic recording medium and magnetic recording medium
JP2018024614A